Assessment of potential concrete and mortar rheometry artifacts using magnetic resonance imaging. (May 2015) - Hafid, H.; Ovarlez, G.; Toussaint, F.; Jezequel, P.H.; Roussel, N.
Abstract: In this paper, we compare macroscopic measurements and local MRI measurements of the behavior of mixtures of natural and crushed sand particles in model yield stress fluids. In doing so, we seek to assess the potential consequences of artifacts on the measurements of the flow curves of mortars and concretes in rheometers. We conclude that, once plug flow is taken into account and corrected, shear-induced particle migration is the dominating artifact for these systems. This shear-induced particle migration occurs for very low strains and is at the origin of a steady state inhomogeneous particle concentration profile. This induced inhomogeneity shall be therefore always present in most concrete rheometers. We extrapolate that shear-induced particle migration could be at the origin of the existing discrepancy between commercially available concrete rheometers. From a measurement point of view, it leads to an underestimation of yield stress and apparent viscosity at low shear rates. Highlights: We use magnetic resonance imaging to assess the local flowing velocities in rheometers. We measure the rheological behavior of suspensions of sands of various shape and roughness. We evaluate the magnitude of rheometric measurement artifacts on model materials. We extrapolate that shear induced migration is the dominant artifact in mortar and concrete rheometry. Our results suggest that this migration is extremely fast and unavoidable.